The rise of regional authority a comparative study of 42 democracies - Hooghe, Liesbet (London Routledge, 2010)
Most countries around the globe have one or two levels of regional or intermediate government, yet we have little systematic idea of how much authority they wield, or how this has changed over time.
Includes bibliographical references and index.
Keywords: Regionalism